المنهج الكلامي عند الإمام أبي الحسن الأشعري وصلته بالتحديات اللفلسفية المعاصرة - Mohamed Zein, Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research focuses on Abu al-Hasan al-Ash`ari’s legacy and how to reconstruct it in order to provide an Islamic response to the contemporary philosophical challenges. It should be noted that these challenges are based on a type of metaphysics and axiology which completely opposed to the Islamic ones. Undoubtedly, the method of reconstruction will be based upon both rational stand and systematic procedures in its approach to the legacy of Abu al-Hasan al-Ash`ari. By doing so, we will be able to come up with a re-reading of that legacy which is consistent and meaningful in its answers to the contemporary philosophical challenges. Obviously Kalam is the discipline within Islamic sciences that furnishes us with the Islamic worldview and its valuational system. It is because the basis of the disagreement between Islam and the contemporary philosophical trends is, essentially, about these two issues. Evidently, it will not include rational or scientific issues but rather will be confined to metaphysical and axiological problems. However, these disagreements are both old and new but their sources are the same fundamental convictions that differentiate Islam from other doctrines. Clearly, then, for the re-reading method the more it opens new horizons for understanding the contemporary philosophical challenges the better it will assist us to reconstruct meaningful alternatives to the contemporary metaphysical and valuational systems.